Reduced Cerebral Glucose Uptake in an Alzheimer’s Rat Model With Glucose-Weighted Chemical Exchange Saturation Transfer Imaging - Chen, Peidong; Shen, Zhiwei; Wang, Qianqian; Zhang, Bingna; Zhuang, Zerui; Lin, Jiefen; Shen, Yuanyu; Chen, Yanzhi; Dai, Zhuozhi; Wu, Renhua (Frontiers in Aging Neuroscience, 2021)
There are evidences that the reduction of cerebral glucose metabolism correlates with disease progression and predicts histopathological diagnosis in AD. In this study, we investigated the in vivo dynamic changes of cerebral glucose uptake using magnetic resonance glucose chemical exchange saturation transfer (GlucoCEST) technique in a rat model of Alzheimer’s disease (AD). Rats in the AD group received an intracerberoverticular injection of 9μl aggregated amyloid Aβ-Protein (25–35) into the right lateral ventricle (n=6); while rats in the control group were administered sterile normal saline (n=6). After 28 days of Aβ25-35 administration, possible structural and metabolic changes of AD brains were analyzed using brain Diffusion Tensor Imaging (DTI) and hippocampus magnetic resonance spectra (MRS). Finally, we used Nissl staining and Morris water maze to confirm the AD model reliability. Compared to the control rats, our results demonstrated a significantly higher brain glucose concentrations and decreased brain glucose uptake in AD brains evidenced by changes of GlucoCEST signal and GCE signal during the progression of glucose infusion (p<0.05). In addition, the concentrations of N-acetyl aspartate and glutamate were significantly decreased in the AD group compared to the control group (P<0.05). Nissl staining verified that AD rats had significantly reduced number of neurons in the cortex and hippocampus (p<0.05). Moreover, AD rats had significantly longer escape latency and decreased number of crossing times compared to rats in the control group at 28 days after Aβ25-35 injection (p<0.05). Taken together, our results suggest abnormal mechanism of brain glucose metabolism in AD rats and offer a new imaging method to observe the changes of brain glucose of AD disease in vivo.